2013
DOI: 10.1177/0040517513487783
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cotton fiber maturity and linear density (fineness) by examination of fiber cross-sections. Part 1: Comparison of two image analysis systems used in conjunction with optical microscopy

Abstract: Researchers from the United States Department of Agriculture and Texas Tech University have published the establishment of a set of reference cottons with known fiber maturity and linear density (fineness) values. Their work was based on careful analysis of the dimensions of a large number of individual transverse fiber cross-sections viewed under the optical microscope to obtain representative values for a particular cotton. Since this set of reference cottons has a high potential value for instrument develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Cross-section area calculation. As reported elsewhere, 13,[15][16][17] cross-section area was used to calculate fineness of polymeric and natural fibers. In our work, several bundles of fibers treated by the above combing operations were cut into slices with clear cross-sections and imaged with scanning electron microscopy (SEM).…”
Section: Methods To Measure Linear Density Of Ptfe Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-section area calculation. As reported elsewhere, 13,[15][16][17] cross-section area was used to calculate fineness of polymeric and natural fibers. In our work, several bundles of fibers treated by the above combing operations were cut into slices with clear cross-sections and imaged with scanning electron microscopy (SEM).…”
Section: Methods To Measure Linear Density Of Ptfe Fibersmentioning
confidence: 99%
“…More importantly, the airflow and cross-section methods applied to analyze the average linear density of irregular fibers have been reported. [13][14][15][16][17][18][19][20][21][22][23] However, almost no study has focused on measuring linear density of PTFE split-film fibers. The purpose of this study is to compare the accuracy of PTFE split-film fiber linear densities obtained from various test methods (gravimetric measurement, cross-section method, theory calculation, airflow measurement, assumption calculation, and vibration method).…”
mentioning
confidence: 99%
“…The average characteristics for these cottons obtained by Hequet (personal communication) are summarized in Table 1. Fiber cross-sections were prepared as described by Higgerson et al, 8 a full implementation of the technique developed by Boylston et al 30,31 Two important features of the process of Boylston et al were (a) a focus on aligning the fiber axis normal to the crosssection plane, to minimize systematic errors due to the cross-sections being cut ''on an angle'', and (b) avoiding fiber swelling during the cross-sectioning process. The aligned fibers, carefully packed inside narrow (1/8 in internal diameter) tubing, were embedded in methyl, butyl, methacrylate (MBM) resin.…”
Section: Methodsmentioning
confidence: 99%
“…32 A revised software system has been developed to overcome this problem. 33 Recently Higgerson et al undertook a study to validate the processes and data reported by Hequet et al 8 A cross-section by cross-section comparison of the results of analyzing a set of captured images analyzed both with the original software (FIAS) and independently developed software demonstrated good agreement in fiber perimeter values, but approximately 20% difference in cell wall area values. It was identified that these differences arise from the limited optical resolution of the captured images such that the two image analysis systems have a different interpretation of the outside boundary of the fiber cross-section.…”
mentioning
confidence: 96%
See 1 more Smart Citation